2019
DOI: 10.1177/0255761419890946
|View full text |Cite
|
Sign up to set email alerts
|

“My voice speaks for itself”: The experiences of three transgender students in American secondary school choral programs

Abstract: With the purpose of furthering lesbian, gay, bisexual, transgender, queer, questioning, and allies/agender/asexual (LGBTQA) dialogue in music education and to improve choral instruction for trans(gender) students, this multiple narrative case study explores the experiences of trans students in secondary school choral music programs in the United States. The emergent research design employed narrative and ethnographic techniques to honor and highlight voices of the three participants. The connection or lack the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 36 publications
1
42
0
Order By: Relevance
“…For peer mentoring to function as a platform for developing resilience, LGBTQIA+ students need to feel safe in the classroom (e.g., Corbitt, 2016; Haywood, 2011). Researchers in music education have found that music classrooms have the potential to provide a safe haven for LGBTQIA+ students (e.g., Minette, 2018; Palkki, 2016). Creating safe spaces may be difficult in some situations; however, for heteronormative conditions that reinforce gender, binary designations can include ensemble names (e.g., men’s and women’s choruses), apparel (e.g., dresses for women, tuxedos for men), and teachers using gendered language in rehearsals (e.g., men and women) (Palkki, 2016).…”
Section: Discussion and Implications For Further Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…For peer mentoring to function as a platform for developing resilience, LGBTQIA+ students need to feel safe in the classroom (e.g., Corbitt, 2016; Haywood, 2011). Researchers in music education have found that music classrooms have the potential to provide a safe haven for LGBTQIA+ students (e.g., Minette, 2018; Palkki, 2016). Creating safe spaces may be difficult in some situations; however, for heteronormative conditions that reinforce gender, binary designations can include ensemble names (e.g., men’s and women’s choruses), apparel (e.g., dresses for women, tuxedos for men), and teachers using gendered language in rehearsals (e.g., men and women) (Palkki, 2016).…”
Section: Discussion and Implications For Further Researchmentioning
confidence: 99%
“…As a consequence, LGBTQIA+ youth also experience increased health issues over those who do not identify as being gay (Marshal et al, 2011). Researchers in music education have recently begun to explore the various complexities that exist in the inclusion of sexuality in the music classroom (e.g., Hendricks & Boyce-Tillman, 2018; Palkki, 2016). These include identity (e.g., McBride, 2017; Natale-Abramo, 2011; Palkki, 2014), transgender students (e.g., Nichols, 2013; Palkki, 2016), and trans*+ students (e.g., Cayari, 2019).…”
mentioning
confidence: 99%
“…So I can't talk about my personal experience with it, but I know people who have." (Joseph interview, March 14, 2016) Additionally, I found Palkki's (2016) discussion of this conflict particularly illuminating and affirming with his statement, "I believe that it is possible for cisgender researchers-remaining ever aware of their cisgender privilege-to use their position in a positive way to bring attention and respect to trans experiences and trans issues" (p. 83). My conversations with Joseph served to illuminate my understanding not just of his experiences but also of my own blind spots, especially my privilege as a straight, white, cisgender male.…”
Section: Finding 6: Joseph's Shared Experiences Reminded Me Of Existimentioning
confidence: 92%
“…Within music education specifically, researchers have suggested non-trans faculty and staff educate themselves about challenges faced by transgender students (Bartolome, 2016;Nichols, 2013;Silveira & Goff, 2016), especially since transgender students are more likely to perceive hostile campus environments than their straight and LGB counterparts (Rankin, 2003;Rankin, Weber, Blumenfeld, & Frazer, 2010;Tetreault, Fette, Meidlinger, & Hope, 2013). Despite the challenges that transgender students face, their experiences are not monolithic, as Palkki (2016) noted in his case study of three transgender choral students. He stated, "It is important to state yet again that trans people are not monolithic.…”
mentioning
confidence: 99%
“…It is likely that MtF students will have entirely different experiences and needs in the choral classroom compared with FtM students. Palkki (2016aPalkki ( , 2016b wanted choral directors to see transgender singers as less of a monolith, emphasizing that there will not be a one-size-fits-all approach to working with them. The inability to generalize the strategies used is referenced in much of the literature (Krell, 2014;Palkki, 2016aPalkki, , 2016bRastin, 2016;Sims, 2017aSims, , 2017b).…”
Section: Future Research and Suggestionsmentioning
confidence: 99%